Prospects and risks of using cryptocurrency in the modern economic space - T. O. Pozhuieva; O. Y. Buhrim (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет, 2023)
The modern information society required the emergence of a new financial means of payment. This means of payment is more innovative than conventional money. This means is called cryptocurrency. The purpose of the article is to assess the prospects and risks of using cryptocurrencies in the current economic environment. The modern information society required a new financial means of payment. This innovative means of payment was a new digital currency – cryptocurrency. Cryptocurrency is digital money used instead of real money. At the same time, cryptocurrencies will not be able to completely replace national currencies in the near future. This is due to the prohibition of certain countries. A serious threat posed by cryptocurrencies is the possibility of illegal activities. Confidentiality and security of cryptocurrency transactions are high. Therefore, the government cannot track any user by their wallet address or monitor their data. Cryptocurrencies can be used to pay for smuggling, drug trafficking, human trafficking, arms sales, and terrorist financing. The risks of cryptocurrencies are also the bankruptcy of exchanges, which will lead to a drop in the cryptocurrency rate and the lack of guarantees. Traditional money is guaranteed by state assets, while cryptocurrencies are not. Cryptocurrencies can be considered a revolutionary tool in the field of monetary payments. Cryptocurrency is a serious competitor to traditional currencies. The high volatility of cryptocurrencies allows them to be used as one of the instruments of an investment portfolio. However, the trends traced in the article suggest that the role of electronic means of payment will continue to grow steadily over time. Today, cryptocurrencies are acquiring such properties as riskiness, decentralization, and alternative nature compared to fiat money. The results of the study prove that despite the multidirectional trends, the role of cryptocurrencies will continue to grow steadily.